Morphofunctional property of liver in late period after surgery with cold plasma hemostasis in experimental conditions - O. Yu. Borodin; Ye. V. Semichev; G. Ts. Dambayev; A. N. Baikov; A. M. Bessonov; M. L. Belyanin; V. D. Filimonov; V. Yu. Ussov; Ye. A. Gereng; Ye. S. Koschevets; M. Yu. Sannikov; P. S. Bushlanov; et al. (Бюллетень сибирской медицины, 2012)
Research of morphofunctional properties that indicate intensity of liver injury when performing cold plasma hemostasis. The operation is an atypical resection of liver left lobe with cold plasma hemostasis. It is performed on white rats. There are a biochemical blood analysis, histological study and MRI-scanning in late period. Morphofunctional changes on the 90th and 180th day are described in the issue.